2000
DOI: 10.1159/000018375
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Viral Warts with Particular Fibrillar Intracytoplasmic Inclusion Bodies

Abstract: A new type of skin wart was observed in a Japanese patient. It was characterized by intracytoplasmic inclusions with a ‘fibrillar’ structure which were distinct from previously described wart-associated inclusions. The papillomavirus (HPV)-group-specific antigen could be detected, but DNA hybridization and PCR amplification using probes or PCR primers specific for the main skin HPV genotypes (including HPV-63 which is also associated with ‘filamentous’ inclusions) were negative. We consider that this cytopathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Egawa et al . recently reported a new type of cutaneous wart that had characteristic ICBs with an eosinophilic fibrillary substance of wire loop‐ or knitting wool‐like appearance 5 . Histologically, our patients are similar to that case.…”
supporting
confidence: 82%
“…Egawa et al . recently reported a new type of cutaneous wart that had characteristic ICBs with an eosinophilic fibrillary substance of wire loop‐ or knitting wool‐like appearance 5 . Histologically, our patients are similar to that case.…”
supporting
confidence: 82%
“…In this report, a nodule resembling a common wart showed fibrillar intracytoplasmic inclusion bodies. These clinical and histopathological characteristics are identical to those of the newly described inclusion wart, 2 except for its brown hue. The colour of the nodule did not represent the darkening sometimes shown by involuting warts, 1 because it developed as a tiny black nodule from the beginning.…”
supporting
confidence: 74%
“…The inclusion bodies were found as eosinophilic homogeneous intracytoplasmic bodies in keratinocytes 1 . On the other hand, a new type of nonpigmented viral wart with peculiar fibrillar intracytoplasmic inclusion bodies was recently described 2 . The causal HPV type was thought to be a new HPV type that had not yet been characterized.…”
mentioning
confidence: 99%
“…The E4 proteins of many papillomaviruses form intracellular structures that are characteristic of the infecting virus type. While this is particularly evident in lesions caused by HPV1 and HPV4 (38), it has been suggested that most cutaneous viruses form some sort of cytoplasmic inclusion (32,46,47,70). By contrast, the E4 proteins of human mucosal viruses do not produce inclusions (19,21,40,42,81).…”
Section: Resultsmentioning
confidence: 99%